Simulation and experimental investigation on adaptive multi-order proportional-integral control for pneumatically actuated active suspension system using knowledge-based fuzzy. (6th September 2011) - Imaduddin, Fitrian; Hudha, Khisbullah; Mohammad, Janatul Islah; Jamaluddin, Hishamuddin
This paper presents an adaptive multi-order proportional-integral (PI) control called knowledge-based fuzzy (KBF) multi-order PI control. The controller consists of the two-control loops namely inner loop controller for force tracking control of the pneumatic actuator and outer loop controller to reject the effects of road-induced disturbances. The outer loop controller utilised KBF multi-order PI control while the on-off controller is used in the inner loop controller to compromise with the existing solenoid valve in the pneumatic actuation system. Performance of the proposed controller is compared with the multi-order PI controller without adaptive scheme as well as the existing passive suspension system. Simulation studies are presented in time domain simulation while the experimental evaluation is conducted on a full-scale quarter car test rig. In general, it can be reported that the proposed control scheme is able to provide significant improvement in terms of body states compared to its counterparts. The proposed scheme is also easy to realise in practice due to its simple structure.